Formulating Global Policies and Strategies for Combating Criminal Use and Abuse of Artificial Intelligence - , Amaka Debie Samuel-Okon; , Omobolaji Olufunmilayo Olateju; , Samuel Ufom Okon; , Oluwaseun Oladeji Olaniyi; , Udochukwu ThankGod Ikechukwu Igwenagu (Archives of Current Research International, 2024)
This study investigates the criminal use and abuse of artificial intelligence (AI), exploring the effectiveness of various mitigation strategies. It employs a mixed-methods approach, combining quantitative data from a survey of 211 experts with qualitative insights from academic, governmental, and industrial publications. The research examines four key hypotheses: the impact of public and organizational awareness, the role of advanced detection technologies, the effectiveness of ethical guidelines, and the influence of penalties and enforcement. The findings reveal that awareness, technology, ethics, and enforcement all contribute to mitigating AI misuse. The study concludes by proposing comprehensive strategies, including targeted awareness campaigns, investment in detection technologies, robust ethical guidelines, and strengthened legal frameworks, to effectively combat the criminal use of AI.